Customizable interdental splinting for repair of pediatric mandibular fractures in children with mixed dentition: A novel technique. (June 2022) - Highland, Julie; Dunya, Gabriel; Teames, Charles; Peacock, Jordan; Yamashiro, Duane; Muntz, Harlan; Park, Albert
Abstract: Objective: Repair of pediatric mandibular fractures (PMFs) can be challenging due to the lack of permanent dentition for immobilization, and the presence of unerupted teeth and growth plates in the mandible limiting the space for fixation. Interdental splinting (IDS) has been advocated to provide temporary fixation without the need for mandibular plating; however, there is sparse description of the surgical methodology, and data on long term outcomes are even more limited. The aim of this study is to present our technique and outcomes using a novel technique for IDS repair of pediatric mandible fractures. Study design: Observational retrospective chart review. Setting: Tertiary care pediatric hospital. Subjects and methods: Pediatric patients requiring operative repair for mandibular fracture at our tertiary care institution between 2004 and 2021 were included. Patients over 18 years of age, those who died due to associated injuries, or those who underwent non-IDS repairs were excluded. Subjects with at least 3 months of follow-up were assessed for efficacy of surgical repair and short-term adverse outcomes, and at least 1 year for long-term adverse events. Descriptive statistics were obtained. Results: Twenty-three children were included in the study with an average age of 7.4 years (range 2–17 years). Fifty-two percent (52.2%) were female. The most common fracture site was the condyle, occurring in 16 children (70%). The indication for operative repair in all cases was malocclusion. The average duration of maxillomandibular fixation (MMF) with the novel IDS was 21 days (range 12–42 days). The average length of follow up was 1.6 years (range 3 months–11 years). All children had restored, functional occlusion at follow up with none requiring further orthodontic or dental intervention. Three children of the total cohort (13.0%) had prolonged hospitalization beyond 48 h for poor oral intake. Five children (21.7%) experienced minor long-term complications including persistent temporomandibular joint pain (n = 1, 4.3%), infection (n = 2, 8.7%), hypertrophic scar (n = 1, 4.3%) and exposure of hardware (n = 1, 4.3%). Conclusion: PMFs resulting in malocclusion are safely and effectively managed with operative repair utilizing a customizable IDS, with few observed short- and long-term complications.